2012
DOI: 10.1002/adfm.201202258
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Continuous Hydrodynamically Controlled Fabrication of Biohybrid Microfibers

Abstract: Cell encapsulation is critical for many biotechnology applications including environmental remediation, bioreactors, and regenerative medicine. Here, the development of biohybrid microfibers comprised of encapsulated bacteria in hydrogel matrices produced on‐chip using microfluidics is reported. The fiber production process utilizes hydrodynamic shaping of a cell‐laden core fluid by a miscible sheath fluid. Production of the fibers containing viable bacteria was continuous in contrast to the more typical metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
66
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 38 publications
0
66
0
1
Order By: Relevance
“…Such a technique provides excellent manipulation on microflow jets, 17, [29][30][40][41][42] showing great potential for manufacturing microfibers with controllable separated external or internal knots. 17, [43][44][45][46][47] By using a microfluidic chip combined with a digital fluid controller and pneumatic valves, spider-silk-like calcium alginate (CaAlg) microfibers with controllable external spindle-knots are developed from jet templates for water collection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such a technique provides excellent manipulation on microflow jets, 17, [29][30][40][41][42] showing great potential for manufacturing microfibers with controllable separated external or internal knots. 17, [43][44][45][46][47] By using a microfluidic chip combined with a digital fluid controller and pneumatic valves, spider-silk-like calcium alginate (CaAlg) microfibers with controllable external spindle-knots are developed from jet templates for water collection.…”
mentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34][35][36][37] Typically, microfibers with separated spindleknots can be achieved by dip-coating of commercial microfibers into polymer solutions. 1,20,38 Thus, polymer solution drops can form along the microfiber due to the Rayleigh instability, and then spindle-knots are generated after evaporating the solvent of the polymer solution drops.…”
mentioning
confidence: 99%
“…This morphology in turns affect the physical features like coefficient of friction , rigidity, lustre, color, and wicking properties. Such fibers are also being considered for applications in tissue engineering (Daniele et al (2013); Polini et al (2010)). …”
Section: Introductionmentioning
confidence: 99%
“…12. Cells can be incorporated in biocompatible hydrogel prepolymers and survive the fabrication process with high viability 22 .…”
Section: Introductionmentioning
confidence: 99%
“…NRL investigators have demonstrated the following critical technical features [13][14][15][16][17][18][19][20][21] :…”
Section: Introductionmentioning
confidence: 99%